Misuse of Rehabilitation Policy in the Narcotics Law: An Analysis of Extortion Practices by Police Officers - Tuasalamony, Adzra Ardelia; Lewoleba, Kayus Kayowuan (Dinasti Research, 2025)
This research analyzes the implementation of rehabilitation policies under Law Number 35 of 2009 on Narcotics and their misuse by certain law enforcement officers. The study focuses on understanding rehabilitation as a right for victims of narcotics abuse and identifying the factors leading to extortion practices. The research employs a normative legal approach combined with statutory, case, and conceptual analyses. The findings reveal that although rehabilitation is regulated as an alternative to imprisonment aimed at health recovery and social reintegration, its implementation faces significant challenges, including limited facilities, social stigma, and unclear technical regulations. These conditions create opportunities for police officers to exploit legal loopholes and the vulnerable position of victims through extortion. Economic motives, social environment, weak internal supervision, and a permissive police organizational culture are identified as the main contributing factors. This study emphasizes the importance of strengthening regulations, enhancing law enforcement accountability, and expanding access to legal aid to ensure that rehabilitation policies truly protect victims and remain free from abuse of authority.